La responsabilidad del adolescente infractor y su inimputabilidad en la Legislación Ecuatoriana. - Punina Ortega, Jean Carlos (2023)
The Constitution of the Republic in its postulate guarantees as a primary duty of the State the effective enjoyment of the rights it enshrines and those recognized by the international instruments to which Ecuador is a party. In this same sense, the Magna Carta according to the Ecuadorian constitutional tradition warns special emphasis on the protection and guarantee of the rights of children and adolescents, considering them as full persons and to that extent subjects of rights; Likewise, it calls them a priority attention group and establishes the obligation of the State to protect it against any type of violence. Regarding the non-imputability of adolescents, the Constitution of the Republic in its Article 77 numeral 13 establishes that “For adolescent offenders, a system of socio-educational measures will govern proportional to the attributed infraction… The deprivation of liberty will be established as last resort, for the minimum necessary period, and will be carried out in establishments other than those for adults. ” Additionally, the Magna Carta determines in Article 11 numeral 8, that “The content of the rights will be developed progressively through regulations, jurisprudence and public policies. The State will generate and guarantee the necessary conditions for its full recognition and exercise. Any action or omission of a regressive nature that unjustifiably diminishes, impairs or annuls the exercise of rights shall be unconstitutional. In this context, there is the protection of rights established in the Constitution of the Republic but it also gives the State the power to generate the necessary conditions for children and adolescents to grow up in a healthy, family environment in order to avoid of adolescence, falling into delinquency. In the present investigation, the actions of adolescent offenders have been analyzed qualitatively in order to determine if it is the family or social environment that induces them to commit infractions or crimes; He also carried out a doctrinal and legal analysis where this problem could be understood. A dialogue was held with adolescents who are within this research environment as well as with legal professionals with whom scientific and empirical information was obtained that contributed to a better understanding of the subject under investigation. The methodology used was exploratory through the study of adolescents from the Guaranda canton, Bolívar province